Pengaruh Model Pembelajaran Kooporatif Tipe Student Teams Achievement Division (STAD) Terhadap Peningkatan Minat Belajar Siswa - Evi Djumiati; Ria Herdhiana; Bella Anantha Sritumini (Program Studi Pendidikan Ekonomi, FKIP Universitas Langlangbuana, 2017)
This research is in the background of the lack of student interest in economic subjects caused by rarely the presence of a teacher in teaching learning, is also found in the learning process in the classroom which only use the usual learning used by teachers, where the learning activities are still centered on the teacher, and there is no interaction in involving students resulting class becomes monotonous and lead to a lack of interest in learning the economic lesson. This research entitled